An Intervention to Increase Situational Awareness and the Culture of Mutual Care (Foco) and Its Effects During COVID-19 Pandemic: A Randomized Controlled Trial and Qualitative Analysis - Kozasa, Elisa H.; Lacerda, Shirley S.; Polissici, Monica Aparecida; Coelho, Roseli da Silva; Farias, Gedeon da Silva; Chaves, Patrícia; Leão, Eliseth R. (Frontiers in Psychiatry, 2020)
Situational awareness is especially important to decision-making in health care. Comprehending the situation is crucial for anticipating any change in the environment and delivering optimal care. The objective of this study was to evaluate the effects of a training to increase situational awareness and mutual care designed for health care workers (FoCo) in a randomized controlled trial with additional qualitative analysis. We also investigated the perception of the training for the COVID-19 pandemic moment, in May 2020, almost six months after we finished the data collection at the Emergency Care Unit, which became a COVID-19 treatment reference for the care of a population depending on the public health system, in Sao Paulo, Brazil. We conclude that FoCo training can be an important instrument for health care professionals both in times of pandemic and “normal times”, to increase situational awareness, the culture of mutual care and decrease the possibility of occupational injuries and illnesses.